Social Media and European Politics : Rethinking Power and Legitimacy in the Digital Era - Barisione, Mauro; Michailidou, Asimina (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2017)
This volume investigates the role of social media in European politics in changing the focus, frames and actors of public discourse around the EU decision-making process. Throughout the collection, the contributors test the hypothesis that the internet and social media are promoting a structural transformation of European public spheres which goes well beyond previously known processes of mediatisation of EU politics. This transformation addresses more fundamental challenges in terms of changing power relations, through processes of active citizen empowerment and exertion of digitally networked counter-power by civil society, news media, and political actors, as well as rising contestation of representative legitimacy of the EU institutions. Social Media and European Politics offers a comprehensive approach to the analysis of political agency and social media in European Union politics, by bringing together scholarly works from the fields of public sphere theory, digital media, political networks, journalism studies, euroscepticism, political activism and social movements, political parties and election campaigning, public opinion and audience studies.
Keywords: Social sciences.; Social media.; Internet marketing.; Europe -- Politics and government.; Political sociology.; elektronické knihy; electronic books